2021
DOI: 10.1097/md.0000000000026358
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effects of sodium hyaluronate, polyethylene glycol, and dextran-70 eye drops in relieving dry eye after phacoemulsification

Abstract: To compare the clinical efficacy of sodium hyaluronate eye drops, polyethylene glycol eye drops, and compound dextran eye drops in the treatment of dry eye after phacoemulsification of cataract. A total of 99 patients with dry eye after cataract phacoemulsification combined with intraocular lens implantation were treated in our hospital. Patients were divided into group A (sodium hyaluronate eye drops), group B (polyethylene glycol eye drops), and group C (dextran-70 eye drops). The clinical effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Dextran‐70, represented in a single study of postoperative cataract patients, given three times daily, was found to be inferior to HA given one to four times daily in all subjective and objective measures (Duan & Tang, 2021), concentrations were not given.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Dextran‐70, represented in a single study of postoperative cataract patients, given three times daily, was found to be inferior to HA given one to four times daily in all subjective and objective measures (Duan & Tang, 2021), concentrations were not given.…”
Section: Resultsmentioning
confidence: 96%
“…Among the 23 included studies, there were two non‐randomised prospective‐longitudinal studies (Benitez‐del‐Castillo et al, 2002; Duan & Tang, 2021) with the remaining 21 studies being randomised controlled trials (RCTs) (Table 1). Seven studies were open‐label (Benitez‐del‐Castillo et al, 2002; Cui et al, 2018; Duan & Tang, 2021; Hwang et al, 2014; Jun et al, 2019; Park et al, 2017; Rolando & Valente, 2007), nine were single blinded (Brignole et al, 2005; Essa et al, 2018; García‐Conca et al, 2019; Gong et al, 2015; Kinoshita et al, 2013; Lee et al, 2011; McCann et al, 2012; Robert et al, 2016; Sanchez et al, 2010), and seven were double‐blinded (Johnson et al, 2008; Lambiase et al, 2017; Lee et al, 2006; Matsuo, 2004; Nelson & Farris, 1988; Takamura et al, 2012; Wu et al, 2021). Two studies had cross‐over design (Essa et al, 2018; Matsuo, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium hyaluronate eye drops are artificial tears which prevent loss of water from the eye surface, in addition to providing a stable tear film and moistening the eyeball, all of which relieve the symptoms of dry eyes and foreign body sensation in patients [17]. However, sodium hyaluronate eye drops contain a small amount of desiccant which irritates the cornea, especially if the drug is used for a long time.…”
Section: Iscussionmentioning
confidence: 99%